Economic determinants of energy intensity: A country panel analysis / Fatemeh Dehdar - Fatemeh , Dehdar (2020)
Efforts to lower energy intensity increased initially as a result of rising fuel prices following the first and second oil shocks, which subsequently became serious owing to mounting evidence that fossil fuels are a major cause of climate change and global warming. Energy source is a key problem associated with climate change as oil and gas, and coal constitute major components of fossil fuels. However, the extant literature remains divided on the determinants of energy intensity. For the purpose of filling this gap, this study modeled energy intensity and used panel annual data from 84 countries, (divided to stable and unstable countries for the second research question) from 1980 to 2012. In order to find out the sign and magnitude of the relationships, the current study applied Generalized Method of Moments (GMM). The first research question investigates the relationship between trade and energy intensity in global panel and the effects of exports, imports and export diversification is tested by including them separately in the energy intensity model. FDI, urbanization and industrialization are also included in the model. Results revealed that trade openness significantly and positively affect energy intensity, through increase in the economic activities. Similarly, exports and imports have significant and positive effects on energy intensity. Export diversification positively and significantly affect energy intensity, determining the fact that the more diversity of exports production, results in less energy intensity. Results show that energy prices and urbanization are not statistically significant in all of the estimations. FDI represents highly significant contribution in improving energy efficiency and decrease of energy intensity in all of the models. Increase in industrialization will lead to increase in energy intensity in all of the estimations. Results of the second research question revealed that, FDI in particular has a highly significant contribution towards lowering energy-intensity, as its coefficients were negative and highly significant at 1 percent in all three groups of countries. However, urbanization had no impact on energy intensity levels in all three groups of countries, while industrialization and trade exacerbated energy intensity in the global panel of countries. Whereas trade showed no relationship with energy intensity among stable and unstable countries, industrialization worsened energy intensity among stable countries. Institutional quality had a highly significant (1 percent) and positive impact on reducing energy intensity in all three groups of countries. The third research question of this study is regarding the direction of relationship between institutional quality and energy intensity in global panel. Prior to Granger causality test, the stationary properties of variables are tested applying Im–Pesaran–Shin (IPS) and Levin–Lin–Chu (LLC) panel unit root tests. Based on the results from these tests, both energy intensity and institutional quality are stationary. Applying GMM estimation, panel VAR model is estimated which is followed by panel VAR Granger causality Wald test. Results of Granger causality test shows that there is unidirectional causality running from institutional quality to energy intensity. The quality of environment is considered as a public good and provision of public goods are affected by the institutional quality.